ChemInform Abstract: Cycloaddition of Keteniminium with Terminal Alkynes Toward Cyclobuteniminium and Their Use in Diels—Alder Reactions. Issue 8 (February 2015) - Lumbroso, Alexandre; Catak, Saron; Sulzer‐Mosse, Sarah; De Mesmaeker, Alain
Abstract Cyclobutinium salts react with dienes to form bicyclic compounds with high regio‐ and stereoselectivities.